جودة أداء معلمة الروضة وأثره على التفاعل الاجتماعي للطفل من وجهة نظر مديرات رياض الأطفال في محافظة اللاذقية - العشعوش أيمن; سليمون ريم; عبد الحميد نور (Latakia University Journal - Economic and Legal Sciences Series, 2016)
The research aims to study the impact of the quality of the kindergarten teacher performance on the social interaction of the child from the standpoint of directors kindergarten in the province of Latakia, and to achieve the objectives of the research were built and distributed a questionnaire on a sample of executives kindergarten included (123) director, was of them (104) questionnaires are valid and complete statistical analysis , adopted Find the descriptive approach, and using appropriate statistical methods was the most important results: The presence of statistically significant relationship between positive and weak quality performance kindergarten teacher and social interaction for the kindergarten child, the higher the quality of any kindergarten teacher performance led to increased social interaction for kindergarten children, and its impact positively on the upbringing. Private kindergarten differ from the public in the quality of performance parameter, where results showed a statistically significant differences between private and public kindergarten children in the quality of performance parameter, and these differences for the benefit of private kindergartens. Assess the quality of the performance of the kindergarten teacher by managers varies depending on years of experience, where results showed that up years of experience in the field of child care, kindergarten increases the ability of managers to evaluate the performance of the kindergarten teacher. يهدف البحث إلى دراسة أثر جودة أداء معلمة الروضة على التفاعل الاجتماعي للطفل من وجهة نظر مديرات رياض الأطفال في محافظة اللاذقية, ولتحقيق أهداف البحث تمّ بناء استبانة وزعت على عينة من مديرات رياض الأطفال شملت (123) مديرة, أعيد منها (104) استبانات صالحة وكاملة للتحليل الإحصائي, اعتمد البحث على المنهج الوصفي, وباستخدام الأساليب الإحصائية المناسبة, وكان من أهم نتائج البحث: وجود علاقة دالة إحصائياً طردية وضعيفة بين جودة أداء معلمة الروضة والتفاعل الاجتماعي لطفل الروضة, أي كلما زادت جودة أداء معلمة الروضة أدى ذلك إلى زيادة التفاعل الاجتماعي لطفل الروضة, وأثر ذلك إيجاباً على تنشئته. تختلف رياض الأطفال الخاصة عن العامة في جودة أداء المعلمة, وقد أظهرت النتائج وجود فروق إحصائية دالة بين رياض الأطفال الخاصة والعامة في جودة أداء المعلمة, وهذه الفروق لصالح رياض الأطفال الخاصة. يختلف تقييم جودة أداء معلمة الروضة من قبل المديرات باختلاف سنوات الخبرة. وقد أظهرت النتائج أنه بارتفاع سنوات الخبرة في مجال رعاية الطفولة, تزداد قدرة مديرات الروضة على تقييم أداء معلمة الروضة.